Analisis Posisi Strategis PT Mayora melalui Pendekatan Matriks IFE, EFE, dan SPACE - Rita Rachmayanti Pasah; Werner R Murhadi (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the strategic position of PT Mayora in facing competition in the food and beverage industry using the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), and SPACE (Strategic Position and Action Evaluation) matrices. The IFE analysis resulted in a score of 2.92, indicating that PT Mayora possesses solid internal strengths, particularly in brand equity, product innovation, and an extensive distribution network. The EFE matrix yielded a score of 2.87, reflecting the company's strong ability to capitalize on external opportunities and manage industry threats. Meanwhile, the SPACE Matrix places PT Mayora in the Aggressive quadrant, signifying a strong financial and competitive position within an attractive and relatively stable industry environment. Accordingly, the recommended strategies are aggressive growth strategies, including market expansion, new product development, technological investment, and potential mergers or acquisitions. These strategies are deemed appropriate to support the company’s long-term vision of strengthening its market dominance both domestically and internationally.